Joint meeting of the I.F.T.U. and L.S.I.. 25 November 1938 - International Federation of Trade Unions ; Labour and Socialist International
017a-0002-001 NCL Joint Meeting of the I.F.T.U. and L.S.I., 25 November, 1938. Agenda: (1) Problems arising out of the situation in Spain. (2) World Peace Campaign. The two Internationals declared that: (a) a settlement of the war in Spain cannot be sought without consultation of the Spanish people, represented by the legitimate Government of the Republic, and that (b) a settlement can only be found on the lines of international law, (which has up till now been held in contempt) by the withdrawal from Spain of all the foreign troops which have invaded it, together with their technicians and the material of war with which they are destroying Spain. The Campaign for world peace and international understanding was referred to the I.F.T.U. Executive and the L.S.I. Bureau for separate discussion, after which a further joint meeting will be held. The meeting also adopted a resolution condemning the persecution of the Jews and sent a message of sympathy to the French T.U.C. 292/946/17a/2